Barkeria wixarika (Laeliinae, Epidendroideae, Orchidaceae), a new species from Nayarit, Mexico - León-Peralta, Cekouat E.; Jones, Jason; Reynaud, Sergio; Pérez-García, Eduardo A. (Phytotaxa, 2024)
Barkeria wixarika is described from Nayarit, Mexico. This new species is morphologically similar to B. uniflora but distinct in its flowering phenology, inflorescence type, petal shape, column morphology, and geographic distribution. Detailed comparisons with related species, including digital plates along with a map highlighting the distribution of the novel species in relation to others are presented. Finally, an updated identification key for Barkeria is provided.